Barnes' notes on the New Testament / complete and unabridged. - Barnes, Albert, 1798-1870 (Grand Rapids, Mich : Kregel Publications, 1962)
Verse-by-verse, the author covers the entire New Testament, carefully and understandably, explaining every verse and offering a practical application for Christian living. -- Unknown
Keywords: Bible. N.T. -- Commentaries